On the growth of analytic functions represented by the Dirichlet series on semistrips - Skaskiv, O. B. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The behavior of the Dirichlet series with null abscissa of absolute convergence is studied on semistrips.